Infantile tremor syndrome secondary to peroral vitamin B12 replacement therapy: a report of two cases with myoclonus - Dilber, Beril; Reis, Gökçe Pınar (The Turkish Journal of Pediatrics, 2021)
Background. Abnormal movements such as tremors and myoclonus may be observed during both treatment and deficiency of vitamin B12, particularly in infants. Infantile tremor syndrome (ITS) is defined by the tetrad of pallor, developmental delay/regression, skin pigmentation, and brown scanty scalp hair. Case. In this report, two cases with ITS aged less than one year who had myoclonic movements during vitamin peroral B12 treatment are discussed based on hematologic, neurological, and magnetic resonance images (MRI) findings, one of whom developed a whole-body tremor and rhythmic myoclonic movements, titubation, and restlessness in the hands and feet as well as diffuse cerebral atrophy on brain MRI. Conclusion. The infants of mothers with nutritional vitamin B12 deficiency may develop sudden abnormal movements following peroral vitamin B12 therapy and that the differential diagnosis of these disorders is highly important for the prevention of long-term neurological sequela by treatment.
Keywords: cerebral atrophy; infantile tremor syndrome; myocolonic movement disorders; peroral vitamin B12 therapy